2017
DOI: 10.4178/epih.e2017007
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to common allergens among patients with allergies in major Iranian cities: a systematic review and meta-analysis

Abstract: Various allergens are implicated in the pathogenesis of allergic diseases in different regions. This study attempted to identify the most common allergens among patients with allergies based on the results of skin prick tests in different parts of Iran. Relevant studies conducted from 2000 to 2016 were identified from the MEDLINE database. Six common groups of allergen types, including animal, cockroach, food, fungus, house dust mite, and pollen were considered. Subgroup analysis was performed to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
5
8
0
Order By: Relevance
“…This is consistent with results reported earlier from the same centre [2]. Similarly, recent meta-analysis regional results [41] documented the high rate of sensitization to local pollens (47%), being responsible for the high prevalence of respiratory allergy in the region. They concluded that sensitization to Alternaria and other non-regional aeroallergens only have a minor influence on asthma patients.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with results reported earlier from the same centre [2]. Similarly, recent meta-analysis regional results [41] documented the high rate of sensitization to local pollens (47%), being responsible for the high prevalence of respiratory allergy in the region. They concluded that sensitization to Alternaria and other non-regional aeroallergens only have a minor influence on asthma patients.…”
Section: Discussionsupporting
confidence: 92%
“…These results can be explained by the assumption that younger children stay more indoor and therefore are more exposed to HDM and cockroaches than older children who play outside baring themselves to animal allergens. Similar conceptual results were found in the following studies: Riyadh (HDM and aspergillus sensitization rates were more common in adults whereas Salsola kali and date palm sanitization were more common in children), 16 Iran (cockroaches sanitization is more prevalent in children <16 years, whereas HDM, pollens, cat dander, and molds were more common in adults >16 years), 20 Jordan (cats and HDM are more common in younger age group) 18 and Saudi Arabia (where HDM is the most prevalent allergen in younger age group). 17…”
Section: Discussionsupporting
confidence: 87%
“…13 Moreover, there was a study in Jordan and two previous studies directed in Iran (one of them was a meta-analysis study) revealed that the most common aeroallergens were pollens followed by HDM and cockroach. [18][19][20] The differences between the results from Gulf states, including ours, with those from Jordan and Iran might be related to genetic, environmental, or geographical/ meteorological factor or even lifestyles.…”
Section: Discussionmentioning
confidence: 65%
“…Assuming that 2.5% of asthmatic patients suffer from ABPA, 38,565 (48.2 per 100,000 general population) patients were estimated to have ABPA in Iran. According to a reported rate of fungal sensitization in adults with asthma (19.6%) [38], a total of 302,356 individuals were estimated. The rate of fungal sensitization rises with asthma severity, so assuming a higher rate of 33% being sensitized to fungi in severe asthma [16], 50,907 asthmatic patients have SAFS.…”
Section: Asthma and Allergic Aspergillosismentioning
confidence: 99%